High internal phase Pickering emulsions stabilized by cellulose nanocrystals for 3D printing. (April 2022) - Ma, Tao; Cui, Ranran; Lu, Shuyu; Hu, Xinna; Xu, Bo; Song, Yi; Hu, Xiaosong
Abstract: A route for creating edible 3D materials is the use of highly concentrated oil-in-water emulsions. In this study, a high internal phase Pickering emulsion (HIPPE) was prepared by centrifuging pre-emulsions at different CNC concentrations. We found that HIPPE with an internal phase volume fraction of 80% can be obtained at 0.5 wt% CNC concentration and 4000 g centrifugal force. The resultant HIPPE exhibited excellent storage stability, apparent shear-thinning behavior, and high solid viscoelasticity, and these properties were successfully applied to 3D printing. We further investigated the effects of pH and ionic strength on the formation and 3D printability of HIPPE. It was shown that HIPPEs can be successfully prepared under pH conditions ranging from 5 to 8, and ionic strength between 25 and 200 mM NaCl. Furthermore, we demonstrated that HIPPE was able to 3D-print selected shapes with high resolution and shape fidelity at pH 7 and 50 mM NaCl. This printed material opens new possibilities for future food manufacturing, nutrition delivery systems, and biomedical tissue engineering. Graphical abstract: Image 1 Highlights: HIPPEs are produced using unmodified CNCs and without adding extra solid particles. The volume fraction of HIPPE stabilized by 0.5 wt% CNCs is up to 80%. HIPPEs exhibit excellent 3D printability due to viscoelastic solid-like behavior. 3D object based on HIPPEs with 0.5 wt% CNCs and 50 mM NaCl shows fine shape.